2011
DOI: 10.1186/1743-422x-8-434
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of sialic acid receptors and influenza A virus of avian and swine origin in experimentally infected pigs

Abstract: BackgroundPigs are considered susceptible to influenza A virus infections from different host origins because earlier studies have shown that they have receptors for both avian (sialic acid-alpha-2,3-terminal saccharides (SA-alpha-2,3)) and swine/human (SA-alpha-2,6) influenza viruses in the upper respiratory tract. Furthermore, experimental and natural infections in pigs have been reported with influenza A virus from avian and human sources.MethodsThis study investigated the receptor distribution in the entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
90
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 43 publications
8
90
1
1
Order By: Relevance
“…However, if the location of avian influenza receptors is taken into consideration, the lack of LPAI virus in the nasal passages may be an accurate observation. In the pig, avian influenza sialic acid receptors were found mainly in the lungs and lower airway and absent in the upper respiratory tract 22, 23. Another factor may be the infectious dose.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the location of avian influenza receptors is taken into consideration, the lack of LPAI virus in the nasal passages may be an accurate observation. In the pig, avian influenza sialic acid receptors were found mainly in the lungs and lower airway and absent in the upper respiratory tract 22, 23. Another factor may be the infectious dose.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that low polymerase activity in pig cells is responsible in part for the low viral titers usually obtained from swine infected with avian influenza virus (10,30,127) and, as a consequence, could also be a contributing factor in inefficient virus spread. Several recent reports indicated that sialic acid receptor distributions in the respiratory tracts of pigs and humans are indeed similar (29)(30)(31), challenging the theory of the pig as a mixing vessel for influenza virus reassortants. The avian influenza virus receptor (NeuAc␣2,3Gal) was found only in bronchioles and alveoli, not in the trachea, emphasizing the resemblance between the two species.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent susceptibility of pigs to both avian and human influenza virus infections may be explained by the presence of receptors for both types of viruses in the upper respiratory tract of pigs (23). However, more recent publications have challenged that notion (29)(30)(31). Another major host range restriction is exerted in the nucleus of the infected cell, where the viral ribonucleoproteins (vRNPs) must interact with cellular cofactors in order to replicate and transcribe the viral genome (reviewed in reference 32).…”
mentioning
confidence: 99%
“…Later studies revealed that viruses infect more than one type of cell, that some cells express more than one type of receptor, 48,68,140 and that after virus entry, cells may cease to express receptors. 142 In the in vitro studies, removal of sialic acid residues with neuraminidase did not prevent infection, 38,43,140 and virus infection of cells with few or no recognized receptors has been reported. 106 In 2 studies, virus attachment did not always correlate with efficient virus replication.…”
Section: Hemagglutinin and Host Cell Receptorsmentioning
confidence: 99%
“…Recent receptor studies on the respiratory tracts of humans and swine have revealed very similar distribution patterns, suggesting that avian viruses could just as readily infect the human respiratory tract as the swine respiratory tract, negating the need of the pig as an intermediate host. 142,147 Avian and human viruses do not readily infect swine, 77 but infection of pigs with intact avian and human viruses has been reported. 77,85 The presence of avian-and human-origin genes in the triple reassortants that comprise most of the influenza viruses currently circulating in swine also provides evidence for such infections.…”
Section: Cross-species Infectionsmentioning
confidence: 99%